Problematyka prawa funeralnego w działalności Rzecznika Praw Obywatelskich - Czerniawski, Ryszard (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
Most of the complaints in the area of the funeral law received by the Ombudsman, although often the complaints refer to human rights and freedoms, have the civil nature. Usually they are not related to violations caused by acts or omissions of bodies, organisations and institutions obliged to respect and implement human rights and freedoms. Nevertheless, these cases are subject to the Ombudsman addresses, primarily to government authorities, aimed at bringing their attention to the inadequacy between funeral law and current practices. In particular, the following issues are being raised in the addresses: the lack of a statutory definition of the right to the grave, fees for the use of infrastructure and other cemetery charges, the right to bury the dead by those who lived with him in an informal relationship, lack of possibility to scatter remains coming from the incineration of corpses in, organised on cemeteries, so called “gardens of memory”
Keywords: ombudsman; grave; death; ashes of the dead